Zinc oxide-zinc ferrite hollow nanoflower composite material as well as preparation method and application thereof

The preparation of zinc oxide-zinc ferrate hollow nanoflower composite material through chemical precipitation method was solved, and the problems of instability and detection height limit of existing ZnO/ZnFe2O4-based nanogas-sensitive materials were solved, and higher gas-sensitive performance and sensitivity were achieved. New ideas for building gas-sensitive sensors are provided.

CN119263338APending Publication Date: 2025-01-07JILIN UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411556524.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing ZnO/ZnFe2O4-based nanogas-sensitive materials have problems such as instability, detection height limit, and small specific surface area, which affects their gas-sensitive performance.

Method used

The zinc oxide-zinc ferrate hollow nanoflower composite material was prepared by chemical precipitation method, and hollow nanoflower spinel structure was formed through precipitation reaction, etching treatment and high-temperature calcination, which improved the specific surface area and gas-sensitive properties of the material.

Benefits of technology

The response speed and recovery speed of gas-sensitive materials are improved, the detection limit is reduced, the adsorption capacity of gas molecules is enhanced, the sensitivity is improved, and the preparation method is simple, environmentally friendly, and large-scale manufacturing is possible.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263338A_ABST
    Figure CN119263338A_ABST
Patent Text Reader

Abstract

The invention provides a zinc oxide-zinc ferrite hollow nanoflower composite material as well as a preparation method and application thereof, and belongs to the technical field of gas sensitive materials. The preparation method comprises the following steps: precipitating zinc acetate, polyvinylpyrrolidone and potassium ferricyanide at room temperature by adopting a chemical precipitation method to obtain solid Zn3 [Fe (CN) 6] 2 nanoparticles; the preparation method comprises the following steps: taking Zn3 [Fe (CN) 6] 2 nanoparticles as a template reactant, etching the Zn3 [Fe (CN) 6] 2 nanoparticles in water-N, N-dimethylformamide to obtain a ZnFe precursor, and carrying out high-temperature calcination treatment on the precursor to obtain the zinc oxide-zinc ferrite hollow nanoflower structure composite material. The ZnO / ZnFe2O4 composite material prepared by the method disclosed by the invention is good in morphology and relatively large in specific surface area, and is of a hollow nanoflower spinel structure. The structure has potential application value in the field of gas sensors, and a new thought is provided for expanding the application of the spinel type semiconductor oxide serving as a sensitive material to construct the gas sensors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gas-sensitive materials, and in particular to a zinc oxide-zinc ferrite hollow nanoflower composite material and a preparation method and application thereof. Background Art

[0002] At present, environmental problems such as air pollution are becoming more and more serious, and the importance of gas sensors has gradually become prominent, which has inspired scientific researchers to study how to improve the gas-sensing properties of gas-sensitive materials. In recent years, reports on sensitive materials have mainly focused on the morphology regulation of the structure of the oxide itself. Compared with a single metal element, the gas-sensing properties of multi-metal oxide semiconductors can be improved not only by regulating the microscopic morphology, but also by adjusting the stoichiometric ratio of different components. Currently, the most studied multi-metal oxide semiconductor materials are mainly spinel-type. The diverse metal ion types, crystal configurations, and defect states make it easier for spinel-structured semiconductor oxides to obtain more excellent properties through composition adjustment and morphology regulation, which is of great significance for the construction of high-performance gas sensors.

[0003] ZnO is one of the most common n-type semiconductors with a wide band gap of 3.37 eV. It has become an important candidate material in the field of gas sensors due to its unique properties such as low cost, scalable manufacturing and diverse nanostructures. At the same time, ZnFe 2 O 4 It is also considered to be a good spinel gas-sensitive material due to its high sensitivity, low operating temperature and excellent response to the measured gas. Many studies have shown that sensing materials composed of two or more metal oxides have better sensing performance than single metal oxides, because heterogeneous structural composite materials are expected to have higher gas-sensitive reaction activity due to the synergistic effect of the components.

[0004] Compared with the structures of other materials, the hollow structure has obvious advantages in sensing performance. The material with a hollow structure can be called a functional material with a void inside, which usually accounts for a large proportion of the total volume. The unique hollow structure not only provides a large specific surface area with abundant active sites, but also provides a short distance for the transmission of charge carriers. In addition, the open hollow structure also provides a channel for the transmission of gas molecules, which can speed up the response speed and the sensing recovery speed. Therefore, the synthesis of mesoporous ZnO / ZnFe with a hollow structure 2 O 4 It has gas-sensitive application value.

[0005] At present, the existing ZnO / ZnFe 2 O 4 Although some progress has been made in improving the gas sensing performance of ZnO / ZnFe 2 O4 Nano-gas-sensitive materials have the problems of instability, high detection limit and small specific surface area. Summary of the invention

[0006] The purpose of the present invention is to provide a zinc oxide-zinc ferrite hollow nanoflower composite material and its preparation method and application, a hollow nanoflower spinel structure gas-sensitive material and its preparation method, so as to solve the problems of spinel-type nano gas-sensitive materials such as instability, high detection limit and small specific surface area, and have excellent gas sensitivity.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a zinc oxide-zinc ferrite hollow nanoflower composite material, comprising the following steps:

[0009] Zinc acetate, potassium ferrocyanide, polyvinyl pyrrolidone and water are mixed to perform precipitation reaction to obtain Zn 3 [Fe(CN) 6 ] 2 Nanoparticles;

[0010] The Zn 3 [Fe(CN) 6 ] 2 The nanoparticles, water and N,N-dimethylformamide are mixed and etched to obtain a ZnFe precursor;

[0011] The ZnFe precursor is calcined to obtain a zinc oxide-zinc ferrite hollow nanoflower composite material.

[0012] Preferably, the mixing of zinc acetate, potassium ferrocyanide, polyvinyl pyrrolidone and water comprises: first mixing zinc acetate and polyvinyl pyrrolidone with water to obtain a mixed solution, second mixing potassium ferrocyanide with water to obtain a potassium ferrocyanide solution, and third mixing the mixed solution with the potassium ferrocyanide solution.

[0013] Preferably, in the mixed solution, the dosage ratio of zinc acetate, polyvinyl pyrrolidone and water is 200-230 mg:490-520 mg:20-30 mL; and the first mixing time is 5-15 min.

[0014] Preferably, in the potassium ferrocyanide solution, the dosage ratio of potassium ferrocyanide to water is 310-340 mg: 20-30 mL; and the second mixing time is 5-15 min.

[0015] Preferably, the third mixing time is 20 to 40 minutes; and the precipitation reaction time is 10 to 30 hours.

[0016] Preferably, the Zn 3[Fe(CN) 6 ] 2 The dosage ratio of nanoparticles, water and N,N-dimethylformamide is 25-40 mg: 3-10 mL: 15-30 mL.

[0017] Preferably, the etching process takes 10 to 20 minutes.

[0018] Preferably, the calcination temperature is 400-700° C., the time is 0.1-4 h, and the heating rate to the calcination temperature is 0.5-2.5° C. / min.

[0019] The present invention provides a zinc oxide-zinc ferrite hollow nanoflower composite material prepared by the preparation method described in the above technical scheme.

[0020] The present invention provides application of the zinc oxide-zinc ferrite hollow nanoflower composite material described in the above technical solution in a gas sensor.

[0021] The present invention provides a method for preparing a zinc oxide-zinc ferrite hollow nanoflower composite material, wherein zinc acetate, polyvinyl pyrrolidone and potassium ferrocyanide are precipitated at room temperature by a chemical precipitation method to obtain a solid Zn 3 [Fe(CN) 6 ] 2 Nanoparticles; Zn 3 [Fe(CN) 6 ] 2 The nanoparticles are used as templates for etching in water-N,N-dimethylformamide to obtain a ZnFe precursor, and the precursor is calcined at high temperature to obtain a zinc oxide-zinc ferrite hollow nanoflower structure composite material.

[0022] ZnO / ZnFe prepared by the method of the present invention 2 O 4 The composite material has a good morphology and presents a hollow nanoflower spinel structure. The unique hollow structure provides a large specific surface area with rich active sites and a short distance for the transmission of charge carriers. The micropores and hollow parts inside the hollow nanoflower structure can serve as channels for gas molecules, accelerating the diffusion of gas molecules on the surface of the material, improving the response speed and recovery speed of gas sensing, and thus improving the gas-sensitive performance of the material; its large specific surface area provides more active sites and enhances the adsorption capacity of gas molecules, thereby improving sensitivity and reducing detection limits. Therefore, this structure has potential application value in the fields of gas sensors, catalytic activation, etc., and provides new ideas for expanding the application of spinel semiconductor oxides as sensitive materials to construct gas sensors.

[0023] The invention does not use conventional solvent thermal reaction, and the product can be obtained under simple room temperature conditions. It is green and environmentally friendly and can be manufactured on a large scale. The product has uniform size, is not easy to agglomerate, and has adjustable morphology and size.

[0024] The preparation method of the invention is simple and easy to implement, adopts common chemical experimental drugs and is low in price. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The etching template Zn in Example 1 3 [Fe(CN) 6 ] 2 Scanning electron microscope images at different magnifications, where (a) is 2 μm and (b) is 500 nm;

[0026] Figure 2 The SEM images of the ZnFe precursor prepared in Example 1 ((a) 2 μm, (b) 500 nm) and the ZnO / ZnFe prepared in Example 1 2 O 4 SEM image (c) and transmission image (d);

[0027] Figure 3 ZnO / ZnFe prepared in Comparative Example 1 2 O 4 SEM images at different magnifications, where (a) is 1 μm and (b) is 500 nm;

[0028] Figure 4 ZnO / ZnFe prepared in Comparative Example 2 2 O 4 SEM image (a) and transmission image (b);

[0029] Figure 5 The etching template Zn prepared in Example 1 3 [Fe(CN) 6 ] 2 X-ray diffraction patterns and corresponding standard cards;

[0030] Figure 6 ZnO / ZnFe prepared in Example 1 and Comparative Examples 1-2 2 O 4 X-ray diffraction patterns and corresponding standard cards;

[0031] Figure 7 The ZnO / ZnFe prepared in Example 1 2 O 4 Element distribution map of hollow nanoflowers;

[0032] Figure 8(a) is the ZnO / ZnFe prepared in Example 1 and Comparative Examples 1-2. 2 O 4 Gas sensitive test results; (b) ZnO / ZnFe prepared in Example 1 and Comparative Examples 1 to 2 2 O 4 Sensitivity curve at 300°C working temperature and n-butanol concentration range of 0 to 1000 ppm. DETAILED DESCRIPTION

[0033] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.

[0034] The present invention provides a method for preparing a zinc oxide-zinc ferrite hollow nanoflower composite material, comprising the following steps:

[0035] Zinc acetate, potassium ferrocyanide, polyvinyl pyrrolidone and water are mixed to perform precipitation reaction to obtain Zn 3 [Fe(CN) 6 ] 2 Nanoparticles;

[0036] The Zn 3 [Fe(CN) 6 ] 2 The nanoparticles, water and N,N-dimethylformamide are mixed and etched to obtain a ZnFe precursor;

[0037] The ZnFe precursor is calcined to obtain a zinc oxide-zinc ferrite hollow nanoflower composite material.

[0038] In the present invention, the mixing of zinc acetate, potassium ferrocyanide, polyvinyl pyrrolidone and water preferably comprises: first mixing zinc acetate and polyvinyl pyrrolidone with water to obtain a mixed solution, second mixing potassium ferrocyanide with water to obtain a potassium ferrocyanide solution, and third mixing the mixed solution with the potassium ferrocyanide solution.

[0039] In the present invention, in the mixed solution, the dosage ratio of zinc acetate, polyvinyl pyrrolidone and water is preferably 200-230 mg:490-520 mg:20-30 mL, more preferably 210-225 mg:500-515 mg:20-30 mL, and further preferably 219 mg:500 mg:25 mL; the first mixing time is preferably 5-15 min, more preferably 7-12 min, and further preferably 10 min.

[0040] In the present invention, in the potassium ferrocyanide solution, the dosage ratio of potassium ferrocyanide to water is preferably 310-340 mg:20-30 mL, more preferably 329 mg:25 mL; the second mixing time is preferably 5-15 min, more preferably 7-12 min, and further preferably 10 min.

[0041] In the present invention, the time of the third mixing is preferably 20 to 40 minutes, more preferably 30 minutes; the present invention preferably pours the potassium ferrocyanide solution into the mixed solution, performs the third mixing under stirring conditions, and then performs a precipitation reaction under static conditions.

[0042] In the present invention, the precipitation reaction time is preferably 10 to 30 hours, more preferably 12 to 24 hours; the precipitation reaction temperature is preferably room temperature.

[0043] During the precipitation reaction, potassium ferrocyanide is ionized into potassium ions and ferrocyanide complex ions ([Fe(CN) 6 ] 3- ), as the reaction proceeds, the zinc ions provided by zinc acetate react with the ferricyanide complex ions to generate water-insoluble Zn 3 [Fe(CN) 6 ] 2 The addition of polyvinyl pyrrolidone helps to control the size and shape of particles and prevent the aggregation of precipitates, thereby improving the quality and performance of the product.

[0044] Spherical Zn 3 [Fe(CN) 6 ] 2 Etching as a template can protect the underlying material from being completely etched away, thereby maintaining the structural integrity of the material and facilitating the formation of a hollow structure.

[0045] After completing the precipitation reaction, the present invention preferably centrifuges and washes the obtained product and dries it in sequence; the reagents used for the centrifugal washing are preferably water and anhydrous ethanol, the rotation speed of the centrifugal washing is preferably 5000-12000 rpm, and more preferably 10000 rpm; the number of times is preferably 3-8 times, and more preferably 4-6 times, and the time of each centrifugation is independently preferably 5-10 minutes, the drying temperature is preferably 55-70°C, and more preferably 60°C; the drying time is preferably 10-14h, and more preferably 12h.

[0046] In the present invention, the Zn 3 [Fe(CN) 6 ] 2The usage ratio of nanoparticles, water and N,N-dimethylformamide is preferably 25-40 mg:3-10 mL:15-30 mL, more preferably 25-35 mg:3-8 mL:20-27 mL, and further preferably 30 mg:5 mL:25 mL.

[0047] In the present invention, the etching treatment time is preferably 10 to 20 minutes, more preferably 10 minutes; the etching treatment is preferably carried out under stirring conditions, and the present invention has no special limitation on the stirring, and stirring can be carried out at a stirring rate well known in the art.

[0048] In the process of the etching treatment, the present invention uses DMF and water for etching treatment, which helps to dissolve the surface components of zinc ferrocyanide, release metal ions, and hydrolyze the zinc ions and iron ions. 3 [Fe(CN) 6 ] 2 A shell of random nanosheets is formed on the template, and as the stirring time continues to increase, the template is eventually completely consumed to obtain a hollow flower structure.

[0049] After completing the etching treatment, the present invention preferably centrifuges and washes the obtained product and dries it in sequence; the rotation speed of the centrifugal washing is preferably 5000-12000 rpm, more preferably 10000 rpm; the number of times is preferably 3-8 times, and the time of each centrifugation is preferably 5-10 minutes, more preferably 10 minutes; the drying temperature is preferably 55-70°C, more preferably 60°C; the drying time is preferably 10-14 hours, more preferably 12 hours.

[0050] In the present invention, the calcination temperature is preferably 400-700°C, more preferably 500-700°C, and further preferably 600-700°C; the time is preferably 0.1-4h, more preferably 0.5-2h, and the heating rate to the calcination temperature is preferably 0.5-2.5°C / min, more preferably 1-2°C / min.

[0051] During the calcination process, as the temperature continues to rise, the adsorbed water in the pores of the precursor is continuously removed. As the temperature continues to rise, the oxidative decomposition of the organic molecules occurs, and the mass is significantly lost. After 600°C, the sample mass is almost not lost, and the carbon component is completely removed to obtain ZnO / ZnFe 2 O 4 Metal oxides.

[0052] The present invention provides a zinc oxide-zinc ferrite hollow nanoflower composite material prepared by the preparation method described in the above technical scheme.

[0053] The present invention provides the application of the zinc oxide-zinc ferrite hollow nanoflower composite material in the above technical solution in a gas sensor. The present invention has no special limitation on the application method, and the application can be carried out according to methods well known in the art.

[0054] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0055] Example 1

[0056] (1) Dissolve 219 mg of zinc acetate dihydrate and 500 mg of polyvinyl pyrrolidone (MW=58000) in 25 mL of deionized water to prepare a mixed solution; dissolve 329 mg of potassium ferrocyanide in 25 mL of deionized water to prepare a potassium ferrocyanide solution. After stirring each for 10 min, the potassium ferrocyanide solution is quickly poured into the mixed solution and stirred for 30 min. The solution is allowed to stand at room temperature for 24 h. The collected precipitate is transferred to a 50 mL centrifuge tube and washed with deionized water and anhydrous ethanol by centrifugation for 4 times alternately at a centrifugal speed of 10000 rpm for 10 min each time. The solution is dried at 60° C. for 12 h to obtain Zn 3 [Fe(CN) 6 ] 2 ;

[0057] (2) Weigh the above Zn 3 [Fe(CN) 6 ] 2 30 mg, dissolved in a mixed solution of water-N,N-dimethylformamide (water = 5 mL, N,N-dimethylformamide = 25 mL) and stirred for etching for 10 min, and the obtained product was centrifuged, washed and dried according to step (1) to obtain a ZnFe precursor;

[0058] (3) The obtained ZnFe precursor was placed in a muffle furnace, the temperature was set to 600 °C, the heating rate was 2 °C / min, and after calcination for 30 min, ZnO / ZnFe 2 O 4 Hollow nanoflower composites.

[0059] Example 2

[0060] The only difference from Example 1 is that the heating rate used in the calcination process in step (3) is 1°C / min, and the rest is the same as Example 1.

[0061] Example 3

[0062] The only difference from Example 1 is that the calcination temperature used in the calcination process of step (3) is 700° C., and the rest is the same as Example 1.

[0063] Comparative Example 1

[0064] The only difference from Example 1 is that the etching step (2) is omitted and the Zn 3 [Fe(CN) 6 ] 2 Calcination was carried out directly, and the calcination conditions and other conditions were the same as those in Example 1.

[0065] Comparative Example 2

[0066] The only difference from Example 1 is that during etching in step (2), the stirring time is 2 minutes, and the rest is the same as Example 1.

[0067] Characterization

[0068] The etching template Zn prepared in Example 1 3 [Fe(CN) 6 ] 2 and ZnO / ZnFe 2 O 4 Analytical characterization of hollow nanoflower composites:

[0069] Figure 1 The etching template Zn in Example 1 3 [Fe(CN) 6 ] 2 Scanning electron microscope images at different magnifications, where (a) is 2μm and (b) is 500nm. It can be seen that the etching template Zn obtained by room temperature coprecipitation method 3 [Fe(CN) 6 ] 2 It has a solid microsphere structure, a rough surface, good dispersibility, and a uniform particle size of about 650 to 800 nm. Its uniform size is a necessary condition for subsequent etching.

[0070] Figure 2 The SEM images of the ZnFe precursor prepared in Example 1 ((a) 2 μm, (b) 500 nm) and the ZnO / ZnFe prepared in Example 1 2 O 4 The scanning electron microscope image (c) and transmission image (d) of the ZnFe precursor can be seen from (a) and (b) that under the etching of the solvent, the ZnFe precursor is composed of many thin nanosheets with huge specific surface area. The thickness of the nanosheets is uniform, about 10-15nm. It can be seen from (c) that at 600℃, the calcined material retains the nanoflower structure well, and the calcined ZnO / ZnFe 2 O 4The surface becomes loose and porous, the surface is rough, and the roughness of the surface is caused by the presence of many interconnected ultra-thin nanosheets. It is worth noting that some nanosheets have curled edges, which indicates that the nanosheets have very thin thickness and even have a certain flexibility. At the same time, observing some broken nanoflower balls can see the hollow structure; from (d), it can be clearly seen that the synthesized sample ZnO / ZnFe 2 O 4 It is an obvious hollow structure, which also confirms the hollow nanoflower structure described in the scanning electron microscope image. It is precisely because of the unique hollow structure and the hierarchical structure constructed by nanosheets that it has a large specific surface area, and the ZnO and ZnFe 2 O 4 The synergistic effect of ZnO / ZnFe 2 O 4 Has excellent sensing performance.

[0071] Figure 3 ZnO / ZnFe prepared in Comparative Example 1 2 O 4 SEM images at different magnifications, where (a) is 1 μm and (b) is 500 nm. It can be seen that the Zn 3 [Fe(CN) 6 ] 2 The morphology obtained by direct calcination is consistent with that of the precursor, except that the surface roughness increases, which is the result of grain quenching caused by the calcination temperature.

[0072] Figure 4 ZnO / ZnFe prepared in Comparative Example 2 2 O 4 The scanning electron microscope image (a) and transmission image (b) of Example 1 are different in that, during the etching process of Example 2, stirring was only performed for 2 minutes. From the broken part of (a), it can be seen that there is a spherical core in the middle of the nanoflower, and from (b), it can be seen that a clear gap is observed between the shell and the core. Therefore, it can be confirmed that when stirring for 2 minutes, the etching degree cannot reach the structure of the hollow nanoflower, and then the intermediate yolk shell nanoflower structure is formed.

[0073] Figure 5 The etching template Zn prepared in Example 1 3 [Fe(CN) 6 ] 2 X-ray diffraction pattern and the corresponding standard card, through the standard card Zn 3 [Fe(CN) 6 ] 2 ·xH 2By comparing the main peak intensities of O (JCPDS: 38-0687), it was found that the prepared material matched the standard spectrum well and had a high-purity phase structure, laying the foundation for subsequent etching.

[0074] Figure 6 ZnO / ZnFe prepared in Example 1 and Comparative Examples 1-2 2 O 4 X-ray diffraction patterns and corresponding standard cards are compared with the simulated ZnO / ZnFe 2 O 4 The main peak intensity comparison of the X-ray diffraction pattern of ZnO and ZnFe 2 O 4 The XRD spectrum shows that the diffraction peaks of the samples can be well indexed as ZnO (JCPDS: 36-1451) and ZnFe 2 O 4 (JCPDS:82-1042), which indicates that the calcined sample is ZnO / ZnFe 2 O 4 Composite materials, no other impurity phase. Compared with the unetched microsphere structure, the yolk shell nanoflower structure and the hollow nanoflower structure have higher crystallinity. In general, the X-ray diffraction pattern is compared with the standard PDF card ZnO (JCPDS: 36-1451) and ZnFe 2 O 4 (JCPDS: 82-1042), the diffraction peaks at 2θ = 31.8°, 34.4°, 36.3°, 62.9°, and 69.1° correspond to the characteristic peaks of the (100), (002), (101), (103), and (201) crystal planes of ZnO, respectively; the diffraction peaks at 2θ = 29.9°, 35.3°, 46.9°, 56.6°, and 62.2° correspond to the characteristic peaks of the ZnFe 2 O 4 The characteristic peaks of (220), (311), (331), (511), and (440) crystal planes indicate that the material prepared by the present invention has good crystallinity and the preparation method is feasible.

[0075] Figure 7 The ZnO / ZnFe prepared in Example 1 2 O 4 The element distribution map of the hollow nanoflowers shows that the elements are evenly distributed, and it can be clearly observed that the synthesized sample is a flower-like structure composed of nanosheets.

[0076] Test Case

[0077] The ZnO / ZnFe prepared in Example 1 2 O 4The gas sensing performance test was carried out using the ZnO / ZnFe prepared in Example 1. 2 O 4 Hollow nanoflowers were used to prepare gas sensors. The performance of the gas sensors was tested using the WS-60A gas sensor performance test system produced by Weisheng Instruments. This system can control the working current of the gas sensor and collect the resistance. The results are shown in Figure 8 ; Wherein, (a) is the ZnO / ZnFe prepared in Example 1 and Comparative Examples 1 to 2 2 O 4 Gas sensitive test results; (b) ZnO / ZnFe prepared in Example 1 and Comparative Examples 1 to 2 2 O 4 At 300℃ working temperature, the sensitivity curve is in the range of 0~1000ppm of n-butanol concentration. Figure 8 It can be seen that the ZnO / ZnFe prepared in Example 1 and Comparative Examples 1-2 2 O 4 Under the condition of 100ppm n-butanol atmosphere, the maximum response value is reached at 300℃, so 300℃ is taken as the optimal working temperature; under the working temperature of 300℃, with the increase of n-butanol concentration, the response sensitivity of the material increases accordingly, and compared with the ZnO / ZnFe prepared in Comparative Examples 1 and 2 2 O 4 The performance has been greatly improved.

[0078] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a zinc oxide-zinc ferrite hollow nanoflower composite material, characterized in that: The following steps are involved: Zinc acetate, potassium ferrocyanide, polyvinyl pyrrolidone and water are mixed to perform a precipitation reaction to obtain Zn3[Fe(CN)6]2 nanoparticles; The Zn3[Fe(CN)6]2 nanoparticles, water and N,N-dimethylformamide are mixed and etched to obtain a ZnFe precursor; The ZnFe precursor is calcined to obtain a zinc oxide-zinc ferrite hollow nanoflower composite material.

2. The preparation method according to claim 1, characterized in that: The mixing of zinc acetate, potassium ferrocyanide, polyvinyl pyrrolidone and water comprises: first mixing zinc acetate and polyvinyl pyrrolidone with water to obtain a mixed solution, second mixing potassium ferrocyanide with water to obtain a potassium ferrocyanide solution, and third mixing the mixed solution with the potassium ferrocyanide solution.

3. The preparation method according to claim 2, characterized in that: In the mixed solution, the dosage ratio of zinc acetate, polyvinyl pyrrolidone and water is 200-230 mg:490-520 mg:20-30 mL; and the first mixing time is 5-15 min.

4. The preparation method according to claim 2, characterized in that: In the potassium ferrocyanide solution, the dosage ratio of potassium ferrocyanide to water is 310-340 mg: 20-30 mL; and the second mixing time is 5-15 min.

5. The preparation method according to claim 2, characterized in that: The third mixing time is 20 to 40 minutes; the precipitation reaction time is 10 to 30 hours.

6. The preparation method according to claim 1, characterized in that: The dosage ratio of the Zn3[Fe(CN)6]2 nanoparticles, water and N,N-dimethylformamide is 25-40 mg: 3-10 mL: 15-30 mL.

7. The preparation method according to claim 1 or 6, characterized in that: The etching process takes 10 to 20 minutes.

8. The preparation method according to claim 1, characterized in that: The calcination temperature is 400-700° C., the time is 0.1-4 hours, and the heating rate to the calcination temperature is 0.5-2.5° C. / min.

9. The zinc oxide-zinc ferrite hollow nanoflower composite material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the zinc oxide-zinc ferrite hollow nanoflower composite material according to claim 9 in a gas sensor.

Citation Information

Cited By

  • Method for constructing semiconductor gas sensor for detecting phosphine gas and application

    CN122690032A